Designing an executive education programme: towards a programme design matrix. (10th June 2016) - McCarthy, Patrick; Sammon, David; O'Raghallaigh, Paidi
Abstract: There are many different types of executive education offerings on the market. These offerings vary in title, duration, accreditation, content, focus, etc.; however, all of these offerings present a common challenge (to those designing them) around the likelihood of their success. For the purposes of this study we are focusing on university accredited executive masters programmes. Existing research over the past 20 years has highlighted certain areas of importance with regard to the design of such executive programmes, from engaging with relevant stakeholders to addressing key elements in the programme design. However, notwithstanding this there is a lack of research providing a comprehensive insight into these key elements of design from all relevant stakeholders' perspectives. Therefore, the aim of this research study is to adopt a multi-case study approach to address this research gap. The findings from this research will be targeted specifically at those stakeholders designing university accredited executive masters programmes, most often referred to as the programme directors. Our research will provide these decision makers with an executive programme design matrix that will contain the key questions that should be asked and answered by the programme director as they design their university accredited executive masters programme.